Medication Adherence and Treatment Outcomes Among Tuberculosis Patients in Jember Regency, East Java, Indonesia - Farida Nur Hamidah; Mustaming Mustaming; Paveena Sonthisombat (Lembaga Publikasi Ilmiah Nusantara, 2026)
Medication adherence remains a critical determinant of tuberculosis (TB) treatment success, particularly in high-burden settings such as Indonesia. Suboptimal adherence contributes to prolonged infectiousness, treatment failure, and the emergence of drug-resistant TB. This study aims to analyze medication adherence and its relationship with treatment outcomes among tuberculosis patients in Jember Regency, East Java, Indonesia. A cross-sectional analytical design was employed involving pulmonary TB patients receiving treatment at community health centers in Jember Regency. Data were collected using structured questionnaires assessing socio-demographic characteristics, health literacy, family support, the role of drug swallowing supervisors (Pengawas Menelan Obat/PMO), and self-reported medication adherence. Treatment outcomes were obtained from medical records. Descriptive and inferential analyses were conducted to examine associations between adherence and treatment outcomes. The findings indicate that the majority of patients demonstrated high medication adherence, which was significantly associated with successful treatment outcomes. Health literacy, effective PMO involvement, and strong family support emerged as key factors influencing adherence. These results are consistent with previous studies conducted in various Indonesian regions, highlighting adherence as a central pathway linking social and health system factors to TB treatment success. In conclusion, strengthening patient education, family engagement, and PMO performance is essential to improving TB treatment outcomes. The study provides empirical evidence to support integrated adherence-focused interventions within primary health care settings.